Kunzima, it’s not for the fainthearted: Narratives of the student representative council in negotiating student leadership in higher education - Hlatshwayo, M. N.; Mfeka, N. N. (South African Journal of Higher Education, 2024)
In this article, we explore and theorise the experiences of seven SRC student leaders in one research intensive university in South Africa. We were interested in understanding / exploring / theorising the narratives of the student representative council on how they conceptualise, negotiate and navigate student leadership in a South African university. We adopted a qualitative case study and employed both semi-structured interviews and a focus group discussion to generate our data. The findings from this research project revealed that the 1) SRC fundamentally believes that they are the only valid and legitimate voice for students in higher education. 2) They also revealed the emergent tensions / conflicts / frustrations between the SRC and the university, with the student leaders feeling that the university is deliberate in its effort at ensuring that students do not feel at home in the academy. And perhaps more troubling, the findings also revealed 3) that at times the SRC has become a heteronormative and patriarchal institution, were women student leaders are treated as the “black nannies” of student leadership. We end the article with some concluding thoughts on the complex and intersectional ways that the SRC socially constructs its role and function in the academy, as well as the need for a system wide overhauling in rethinking / reimagining / reconstructing student leadership beyond the colonising, patriarchal gaze.